Vital signs : medical realism in nineteenth-century fiction - Rothfield, Lawrence, 1956- (Literature in history (Princeton, N.J.), 1992)
Vital Signs offers both a compelling reinterpretation of the nineteenth-century novel and a methodological challenge to literary historians. Rejecting theories that equate realism with representation, Lawrence Rothfield argues that literary history forms a subset of the history of discourses and their attendant practices. He shows how clinical medicine provided Balzac, Flaubert, Eliot, and others with narrative strategies, epistemological assumptions, and models of professional authority. He also traces the linkages between medicine's eventual decline in scientific and social status.